Analisis Pengaruh Laba Akuntansi, Arus Kas Operasi, dan Arus Kas Investasi Terhadap Return Saham pada Perusahaan Infrastruktur yang Terdaftar di Bursa Efek Indonesia Periode 2017-2020 - Maulana, Huda (Jurnal KIAFE, 2021)
This study aims to provide an overview and information to interested parties in making decisions, especially in the world of capital markets and investment. In addition to providing clarity for stakeholders in making financial decisions, this study will also examine what factors can be used in estimating the amount of return or rate of return that will be achieved by interested parties later. In this study, the independent variables used were accounting profit, operating cash flow and investment cash flow. While the dependent variable in this study is stock returns. The population of this study amounted to 57 companies in the infrastructure sector listed on the Indonesia Stock Exchange (IDX) in 2017 "“ 2020. The determination of the sample was carried out using the purposive sampling method so as to obtain a sample of 17 companies or 68 research data. The research method used in this study is descriptive analysis method with multiple linear regression analysis and using SPSS version 25. The results showed that the investment cash flow variable had no effect on stock returns, while the accounting profit variable and operating cash flow variable had a positive effect on stock returns. Keywords: Accounting Profit, Operating Cash Flow, Investment Cash Flow, Stock Return.